Truck Fudeau: Algorithms, Conspiracy and Radicalization - Michael Hoechsmann; Miranda McKee (Norteamérica)
COVID-19 public health mandates used in Canada and elsewhere proved to be potent measures for radicalizing new groups to right-wing ideas and gatherings, as well as for broadly main-streaming anti-government and anti-media rhetoric. This is visible online on the sites of some influencers who have waged a battle against COVID-19 mandates, and in real world protests such as Canada’s Freedom Convoy, an event that culminated in a three-week occupation of Canada’s capital, Ottawa, from January 29 through February 20, 2022. The movement had some appeal beyond its core groups and picked up momentum as time went on. The rise of right-wing populism in Canada is a result of multiple factors, but in this article, we will limit the purview to how an anti-vax and anti-mandate movement served to radicalize newcomers to a position antithetical to that of public health authorities and mainstream opinion, and also how this ideological struggle was mobilized and received via algorithm-driven online media.